A Robust Fuzzy Sliding Mode Controller Synthesis Applied on Boost DC-DC Converter Power Supply for Electric Vehicle Propulsion System. (23rd May 2013) - Allaoua, Boumediène; Mebarki, Brahim; Laoufi, Abdellah
Abstract : The development of electric vehicles power electronics system control comprising of DC-AC inverters and DC-DC converters takes a great interest of researchers in the modern industry. A DC-AC inverter supplies the high power electric vehicle motors torques of the propulsion system and utility loads, whereas a DC-DC converter supplies conventional low-power, low-voltage loads. However, the need for high power bidirectional DC-DC converters in future electric vehicles has led to the development of many new topologies of DC-DC converters. Nonlinear control of power converters is an active area of research in the fields of power electronics. This paper focuses on a fuzzy sliding mode strategy (FSMS) as a control strategy for boost DC-DC converter power supply for electric vehicle. The proposed fuzzy controller specifies changes in the control signal based on the surface and the surface change knowledge to satisfy the sliding mode stability and attraction conditions. The performances of the proposed fuzzy sliding controller are compared to those obtained by a classical sliding mode controller. The satisfactory simulation results show the efficiency of the proposed control law which reduces the chattering phenomenon. Moreover, the obtained results prove the robustness of the proposed control law against variation of the load resistance and the input voltage of the studied converter.